2005
DOI: 10.1038/sj.bjp.0706210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of bisindolylmaleimide PKC inhibitors on p90RSK activity in vitro and in adult ventricular myocytes

Abstract: 1 Bisindolylmaleimide inhibitors of protein kinase C (PKC), such as GF109203X and Ro31-8220, have been used to investigate the roles of PKC isoforms in many cellular processes in cardiac myocytes, but these agents may also inhibit p90 RSK activity. 2 In in vitro kinase assays utilising 50 mM [ATP], GF109203X and Ro31-8220 inhibited p90 RSK isoforms (IC 50 values for inhibition of RSK1, RSK2 and RSK3, respectively, were 610, 310 and 120 nM for GF109203X, and 200, 36 and 5 nM for Ro31-8220) as well as classical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 52 publications
0
23
1
Order By: Relevance
“…These early studies also established that PKD expression in myocardial tissue and isolated myocytes is subject to developmental regulation and declines significantly in adulthood. 49 More recent work in our laboratory and by others has confirmed the expression of PKD protein in neonatal 44,52,53 and adult 54,55 rat ventricular myocytes and adult mouse, 44,52 rat, 44 rabbit, 56 and human 56 myocardium. In common with several other genes, cardiac PKD expression appears to revert to the fetal phenotype in disease, with evidence of increased expression in failing rat, 44 rabbit, 56 and human 56 myocardium.…”
Section: Expression and Regulationmentioning
confidence: 86%
See 1 more Smart Citation
“…These early studies also established that PKD expression in myocardial tissue and isolated myocytes is subject to developmental regulation and declines significantly in adulthood. 49 More recent work in our laboratory and by others has confirmed the expression of PKD protein in neonatal 44,52,53 and adult 54,55 rat ventricular myocytes and adult mouse, 44,52 rat, 44 rabbit, 56 and human 56 myocardium. In common with several other genes, cardiac PKD expression appears to revert to the fetal phenotype in disease, with evidence of increased expression in failing rat, 44 rabbit, 56 and human 56 myocardium.…”
Section: Expression and Regulationmentioning
confidence: 86%
“…49 Subsequent work by us and others has confirmed the ability of a variety of stimuli (eg, norepinephrine, 53 the ␣ 1 -adrenergic agonist phenylephrine, 44,53 ET1, 44,53,55 angiotensin II, 53 aldosterone, 52 phorbol ester, 44,[53][54][55] and FBS 44 ) to induce PKD activation in neonatal and adult ventricular myocytes. In many cases, PKD activation was shown to be attenuated by PKC inhibition, 44,[53][54][55] highlighting the critical role of PKC isoforms in neurohormonal regulation of PKD activity in cardiac myocytes. Recently, we have reported evidence that PKC plays a key role in ET1-induced PKD activation in adult rat ventricular myocytes, 55 which is consistent with data on ␣ 1 -adrenergic PKD activation in neonatal myocytes, 53 and demonstrated that ET1-induced, PKC-mediated PKD activation is counteracted by protein kinase A (PKA) activation.…”
Section: Expression and Regulationmentioning
confidence: 99%
“…Figure 1D and 1E shows that NE induces a relatively modest increase in AKT phosphorylation (relative to the considerably more robust response triggered by heregulin or H 2 O 2 ) and that NE-dependent AKT activation is markedly augmented (approaching levels in heregulin-or H 2 O 2 -treated cultures) when cultures are pretreated with GF109203X, but not Go6976. Figure 2A shows that NE-dependent AKT activation is not influenced by U0126, effectively excluding a potential regulatory role for ribosomal S6 kinase (a GF109203X-sensitive enzyme and downstream target of the ␣ 1 -AR/nPKC signaling pathway 9 ). The effect of NEϩGF109203X to increase AKT phosphorylation is sustained for at least 30 minutes; GF109203X alone does not significantly alter basal AKT phosphorylation ( Figure 1E).…”
Section: Methodsmentioning
confidence: 99%
“…7 Briefly, bacterial expression vectors (pGEX-KG or pGEX-3X) encoding aa 516-815, 516-630, 625-747, 748-815 or 625-815) of human NHE1 (the latter with or without the indicated Ser/Ala mutations), Nterminally linked to GST, were transformed into BL21 strain of Escherichia coli. Cultures were grown to sub-log phase and induced with 0.5 mmol/L isopropyl-β-D-thiogalactopyranoside.…”
Section: : Supplementary Materials and Methodsmentioning
confidence: 99%
“…2 Although basal activity of the sarcolemmal NHE is low under physiological conditions, 2 increased exchanger activity may mediate inotropic responses to neurohormonal stimuli, such as endothelin-1, 3 angiotensin II, 4 and ␣ 1 -adrenoceptor agonists, 5 principally through NHE1-mediated increases in intracellular sodium. 6,7 The regulation of NHE1 activity in such settings involves modification of the intracellular carboxyl-terminal regulatory domain of the exchanger, either by the binding of accessory proteins (such as calcineurin homologous protein, 8 carbonic anhydrase II, 9 and calmodulin [CaM] 10 ) and/or by phosphorylation by protein kinases (such as the extracellular signal-regulated kinases [ERKs], 11 p90 ribosomal S6 kinase [RSK], 12,13 Rho-associated kinase [p160-ROCK)], 14 and p38 mitogen-activated protein kinase [p38-MAPK] 15 ). Although the majority of studies have linked protein kinase-mediated phosphorylation of the NHE1 carboxyl-terminal regulatory domain to the upregulation of NHE1 activity, [11][12][13][14][15] there are reports that certain protein kinase pathways can inhibit NHE1.…”
Section: T He Namentioning
confidence: 99%